(untitled) (Journal of Economic Research & Business Administration, 2024)
Social inequality has always been and remains one of the key problems of any economic system, to which both society itself and the state as a whole pay attention. In the article, this problem is inextricably linked with such aspects of state economic regulation as taxation, insurance, investment, which requires a special study of all criteria and indicators for the effective provision of social security of the population. The purpose of the study is to analyze social inequality in Kazakhstan using modern statistical methods such as cluster analysis and ARIMA modeling. The scientific significance of the study is that it presents new insights to the analysis and modeling of social inequality in Kazakhstan. Practical significance can be observed in the analysis of parameters and dynamics of social inequality, which allows to identify vulnerable groups and focus on improving their social situation. Cluster analysis is carried out because of data on social and economic characteristics of the population, to identify groups similar in terms of well-being. The ARIMA (Autoregressive Integrated Moving Average) method is used to model the dynamics of social inequality. The results of the study allowed us to identify the main parameters of social inequality in Kazakhstan. It was found that income inequality remains one of the most significant factors affecting the welfare of the population. Also, significant differences are observed in the level of education, access to health care and quality of housing conditions. The study represents an important contribution to the understanding of social inequality in Kazakhstan, its parameters, and dynamics, as it allows us to assess the scale and structure of social inequality in Kazakhstan. Identify the most vulnerable groups of the population and identify the causes of their vulnerability. To develop forecasts for the development of social inequality and assess possible risks. Key words: social inequality, poverty, employment, unemployment